2023
DOI: 10.1186/s12913-023-09464-x
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and job stressors among healthcare workers who served COVID-19 patients in Bangladesh

Abstract: Background The global outbreak of COVID-19 has created unprecedented havoc among health care workers, resulting in significant psychological strains like insomnia. This study aimed to analyze insomnia prevalence and job stressors among Bangladeshi health care workers in COVID-19 units. Methodology We conducted this cross-sectional study to assess insomnia severity from January to March 2021 among 454 health care workers working in multiple hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Government intervention has a more positive impact on NMT workers. Previous studies also observed doctors and nurses to be the worst sufferers of sleep disorders among all categories of HCWs (Rahman et al, 2023).…”
Section: Comparative Analysis Of Constructs Across Demographic Variab...mentioning
confidence: 81%
See 1 more Smart Citation
“…Government intervention has a more positive impact on NMT workers. Previous studies also observed doctors and nurses to be the worst sufferers of sleep disorders among all categories of HCWs (Rahman et al, 2023).…”
Section: Comparative Analysis Of Constructs Across Demographic Variab...mentioning
confidence: 81%
“…Voluminous studies have revealed the presence of stress, anxiety, insomnia and fatigue during COVID-2019 (Lee et al, 2020;Chew et al, 2020 ;Roy et al, 2020). A few studies have measured insomnia/sleep quality as a measure of stress (Rahman et al, 2023;Xiao et al, 2020) and suggested that job-related stresses and uncertainty during COVID-19 pandemic has affected the mental health and sleep pattern of HCWs. Keeping in view the consequences of psychological stress on health and wellbeing of HCWs, it is essential to measure this construct, which has been extensively taken up in many studies.…”
Section: Construction Of Variables and Development Of Hypothesesmentioning
confidence: 99%
“…The existing literature on Covid-2019 reveals that substantial proportion of HCWs suffered from mental health issues ranging from psychological distress, burnout, anxiety disorders, depression and other issues such as poorly perceived self-health, occupational stress, troubled sleep and insomnia, lack of interpersonal communication and social support, role conflict and lack of control over their lives especially during the period of quarantine 12,[20][21][22][23][24][25][26][27] . Many biological (mood disorder and age), psychological (avoidant personality traits, facing conflict between the familial and professional roles and escaping coping mechanism), and socio-environmental factors (insufficient communication and unsatisfactory information, high risk of exposure to infection to family members, social distancing leading to lack of emotional support, inadequate supply of personal protective equipment) that contributed to the mental health problems of the HCWs have been underlined by multiple studies 8,15,[28][29][30][31][32][33] .…”
Section: Review Of Existing Researchmentioning
confidence: 99%